Pesticide exposure in New Zealand school-aged children: Urinary concentrations of biomarkers and assessment of determinants. (May 2022) - Li, Yan; Wang, Xianyu; Feary McKenzie, Jean; 't Mannetje, Andrea; Cheng, Soo; He, Chang; Leathem, Janet; Pearce, Neil; Sunyer, Jordi; Eskenazi, Brenda; Yeh, Ruby; Aylward, Lesa L.; et al.
Graphical abstract: Highlights: Urinary pesticide metabolites are measured in New Zealand children for the first time. TCPy and PYR levels are higher than measured in other countries. TCPy levels are higher for children living on a farm. Rural residence, dog ownership, and in-home pest control increase pyrethroid exposure. Abstract: This study aimed to assess pesticide exposure and its determinants in children aged 5–14 years. Urine samples (n = 953) were collected from 501 participating children living in urban areas (participant n = 300), rural areas but not on a farm (n = 76), and living on a farm (n = 125). The majority provided two samples, one in the high and one in the low spraying season. Information on diet, lifestyle, and demographic factors was collected by questionnaire. Urine was analysed for 20 pesticide biomarkers by GC–MS/MS and LC-MS/MS. Nine analytes were detected in > 80% of samples, including six organophosphate insecticide metabolites (DMP, DMTP, DEP, DETP, TCPy, PNP), two pyrethroid insecticide metabolites (3-PBA, trans-DCCA), and one herbicide (2, 4-D). The highest concentration was measured for TCPy (median 13 μg/g creatinine), a metabolite of chlorpyrifos and triclopyr, followed by DMP (11 μg/g) and DMTP (3.7 μg/g). Urine metabolite levels were generally similar or low compared to those reported for other countries, while relatively high for TCPy and pyrethroid metabolites. Living on a farm was associated with higher TCPy levels during the high spray season. Living in rural areas, dog ownership and in-home pest control were associated with higher levels of pyrethroid metabolites. Urinary concentrations of several pesticide metabolites were higher during the low spraying season, possibly due to consumption of imported fruits and vegetables. Organic fruit consumption was not associated with lower urine concentrations, but consumption of organic food other than fruit or vegetables was associated with lower concentrations of TCPy in the high spray season. In conclusion, compared to other countries such as the U.S., New Zealand children had relatively high exposures to chlorpyrifos/triclopyr and pyrethroids. Factors associated with exposure included age, season, area of residence, diet, in-home pest control, and pets.